Effects of the use of bio-additives for fuel in metallic gasoline tanks - Celic Cano Romero; Rogelio Cuevas García; Diego Adrián Fabila Bustos; Prisciliano Hernández Martínez; José R. Contreras Bárbara; Macaria Hernández Chávez (Journal of Materials Science: Materials in Engineering)
Abstract Bio-additives, generally composed of alcohol or esters, are sustainable substances added to fuels to enhance their properties and reduce CO2 emissions. In Mexico, there is a lack of regulations on bio-additive-gasoline mixture composition and effects this composition on the mechanical properties of the tanks is not clear. This study investigates the impact of the quantity of a bio-additive added to gasoline on metallic automotive and motorcycle tanks. Two experimental setups were developed: immersion tests in gasoline-bio-additive mixtures at varying concentrations of a sheet of automotive tanks, and exposure of motorcycle metallic tanks to ambient pressure–temperature conditions over 14 months. Corrosion signs and sediment accumulation appeared within 2 weeks, particularly in the 30% bio-additive mixture, pointing to compatibility issues. Characterization methods, including Raman spectroscopy, gas chromatography-mass spectrometry (GC–MS), Electron microscopy (SEM/EDS), and metallography, revealed methanol in the bio-additive composition. Methanol increases corrosion of the automotive sheets, also, it causes the removal of lead from the anticorrosion coating that covers the motorcycle tanks. This results, emphasize the compatibility challenges between bio-additives and all components of the metallic tanks.